2014
DOI: 10.5430/jnep.v4n2p243
|View full text |Cite
|
Sign up to set email alerts
|

The role of nursing in pediatric palliative home care – Experiences from Lower Saxony, Germany

Abstract: Background: In 2007, the patient's right to specialized pediatric palliative home care (SPPHC) became law in Germany. In Lower Saxony, a German federal state with a low population density, an adequate care for children suffering from life-limiting conditions (LLC) should be ensured in the context of low patient numbers and low numbers of specialists. A close cooperation with regional primary health care providers can facilitate the performance of this task. Nursing home services play a decisive role in deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…An increased, more well‐defined collaboration between paediatric clinics and home healthcare teams would prove a significant complement, as confirmed by previous research (Kremeike et al . ). The results of this study revealed that the paediatric clinic was seen as an important source of knowledge.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An increased, more well‐defined collaboration between paediatric clinics and home healthcare teams would prove a significant complement, as confirmed by previous research (Kremeike et al . ). The results of this study revealed that the paediatric clinic was seen as an important source of knowledge.…”
Section: Discussionmentioning
confidence: 97%
“…, , Quinn & Bailey , Reid , Kremeike et al . ), but there is a limited amount of research on how community nurses experience home caring of children with chronic conditions that are not of palliative nature. Considering the positive effects that optimal home healthcare provision may have on families with children suffering from long‐term or complex conditions, we found it important to examine nurses’ experiences in this regard.…”
Section: Introductionmentioning
confidence: 99%